2016
DOI: 10.4315/0362-028x.jfp-16-216
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Selective Conditions to Microbial Competition in Four Listeria Selective Enrichment Formulations

Abstract: Microbial competition during selective enrichment negatively affects Listeria monocytogenes populations and may hinder the subsequent detection or recovery of this organism. Competition assays among 10 selected strains of Listeria and Citrobacter braakii were performed in buffered Listeria enrichment broth, 3-(N-morpholino)propanesulfonic acid–buffered Listeria enrichment broth, University of Vermont medium–modified Listeria enrichment broth, and Fraser broth. The individual contributions of each selective age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…L. seeligeri detection with the USDA method also may be challenging; our data indicated limited growth in the primary UVM enrichment culture. These data for L. seeligeri are consistent with those of three other studies, which indicated that L. seeligeri may not be recovered after enrichment in UVM or Fraser (31) and may not be detected on ALOA (68) or BBL CHROMagar Listeria (another selective and differential agar targeting PI-PLC activity) (24). We located only one study in which growth of L. ivanovii was evaluated in Fraser, and L. ivanovii did not grow after 24 h in this medium (59).…”
Section: Discussionsupporting
confidence: 91%
“…L. seeligeri detection with the USDA method also may be challenging; our data indicated limited growth in the primary UVM enrichment culture. These data for L. seeligeri are consistent with those of three other studies, which indicated that L. seeligeri may not be recovered after enrichment in UVM or Fraser (31) and may not be detected on ALOA (68) or BBL CHROMagar Listeria (another selective and differential agar targeting PI-PLC activity) (24). We located only one study in which growth of L. ivanovii was evaluated in Fraser, and L. ivanovii did not grow after 24 h in this medium (59).…”
Section: Discussionsupporting
confidence: 91%
“…In the Liao et al study, the distribution areas of phylogroups L1 ( L. monocytogenes lineage III), L3 ( L. monocytogenes lineage I), L6 ( L. innocua ), and L8 ( L. welshimeri ) contained the GSMNP region, and L3 and L6 were actually isolated from the GSMNP region ( 15 ); however, none of these phylogroups was isolated in the present study, which may indicate that they were not present in the samples. Alternatively, these phylogroups may have been present in the samples but not recovered; for example, they could have been suppressed or outcompeted by other strains during the enrichment step ( 47 53 ), or their colonies may have simply not been selected off the modified Oxford agar plates for isolation and characterization.…”
Section: Resultsmentioning
confidence: 99%
“…No serotype nor lineage bias was observed in buffered Listeria enrichment broth (BLEB) in a study by Gorski et al (2006). Keys et al (2016) obtained the highest Listeria populations in selective enrichments by adding sodium chloride and lithium chloride at higher temperatures (35°C versus 30°C). The authors pointed out the limited number of selective substances for use in Listeria-specific enrichment media and thus resulting in only limited selective formulations.…”
Section: Methodologies For Recovery Of Listeria Monocytogenes and Oth...mentioning
confidence: 98%
“…The selective enrichment step is further complicated in challenging environments such as soils, where bacterial competition may play a role and lead to the loss of L. monocytogenes and other Listeria species ( Keys et al, 2016 ; Zilelidou et al, 2016 ). It has even been observed that certain L. monocytogenes genotypes outcompete each other: In selective enrichment UVM, lineage I strains are displaced by lineage II strains ( Etty et al, 2019 ).…”
Section: Methodologies For Recovery Of Listeria Monocytogen...mentioning
confidence: 99%